Index to new taxa and nomenclatural acts in Phytotaxa 8 - Christenhusz, M. J. M. (Phytotaxa, 2014)
This paper provides an index to new taxa and nomenclatural acts published in Phytotaxa 8. There are 11 new names for species. There are 12 new combinations.